Ability, Motivation, and Compensation on Performance: Job Satisfaction as Mediator in Mahkamah Syar’iyah Aceh - Irwan Irwan (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya, 2026)
Objective – This study investigates the influence of ability, motivation, and compensation on employee performance at Mahkamah Syar’iyah Aceh, specifically focusing on the mediating role of job satisfaction. Design/Methodology/Approach – A quantitative survey approach was employed, utilizing primary data from employee questionnaires. Hypotheses were tested using Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate both direct and indirect effects. Findings – Ability, motivation, and compensation significantly enhance job satisfaction but exert no significant direct effect on employee performance. Job satisfaction fully mediates the relationship between these antecedent variables and employee performance. Implications – Performance improvements in this judicial context are not automatic results of augmented inputs but strictly require the elevation of job satisfaction. Theoretically, this study clarifies human resource mediation mechanisms within public sector institutions. Practically, organizational leadership must prioritize satisfaction-oriented management strategies over direct compensation or ability-focused interventions to optimize employee performance.